If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6 = 2(x + 8) Reorder the terms: 6 + 4x = 2(x + 8) Reorder the terms: 6 + 4x = 2(8 + x) 6 + 4x = (8 * 2 + x * 2) 6 + 4x = (16 + 2x) Solving 6 + 4x = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6 + 4x + -2x = 16 + 2x + -2x Combine like terms: 4x + -2x = 2x 6 + 2x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 6 + 2x = 16 + 0 6 + 2x = 16 Add '-6' to each side of the equation. 6 + -6 + 2x = 16 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 16 + -6 2x = 16 + -6 Combine like terms: 16 + -6 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| 3x=7x-20 | | 7x-3=5-2x | | 3x-2x+1=x+6 | | 3x+11+7x+3=180 | | 12=3(x-9) | | 3x+5x+10=10x-2x+10 | | 12z^3=14z^2+48z | | 2x+18=4x+10 | | 7-4y=7 | | -9x-5y=27 | | 2*(ln(x))+1=0 | | x-4(x+3)=12 | | 8q+5=2 | | 50q-43=52q-18 | | 250=14w+9g | | 6x-1=7(x+9) | | 2(x-8)=2x+6 | | 2x^2+10X+3=3 | | 4.5g+0.75=18.75 | | 4.5+0.75=18.75 | | 3x=5(x+3)-s | | f(x)=3x^2-9x+6 | | -4=2-3p | | 4k-5=-17 | | -15r+5=50 | | x+4x+(4x-49)=437 | | 5(x-4)+3=7x | | 3x^2-2x-30=0 | | 18=5p-2 | | 60xn=120 | | 8xn=32000 | | 7(x-4)+8x=12+14 |